2007
DOI: 10.1128/mcb.00630-07
|View full text |Cite
|
Sign up to set email alerts
|

Keap1 Controls Postinduction Repression of the Nrf2-Mediated Antioxidant Response by Escorting Nuclear Export of Nrf2

Abstract: The transcription factor Nrf2 regulates cellular redox homeostasis. Under basal conditions, Keap1 recruits Nrf2 into the Cul3-containing E3 ubiquitin ligase complex for ubiquitin conjugation and subsequent proteasomal degradation. Oxidative stress triggers activation of Nrf2 through inhibition of E3 ubiquitin ligase activity, resulting in increased levels of Nrf2 and transcriptional activation of Nrf2-dependent genes. In this study, we identify Keap1 as a key postinduction repressor of Nrf2 and demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
261
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(278 citation statements)
references
References 51 publications
15
261
0
2
Order By: Relevance
“…Consistent with the expression pattern in the literature (29,60,61), NRF2 immediately translocates to the nucleus in response to plasma and binds to ARE sequences in the promoters of its target genes. Afterward, a significant mRNA expres-FIGURE 9.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with the expression pattern in the literature (29,60,61), NRF2 immediately translocates to the nucleus in response to plasma and binds to ARE sequences in the promoters of its target genes. Afterward, a significant mRNA expres-FIGURE 9.…”
Section: Discussionsupporting
confidence: 83%
“…Under basal conditions, NRF2 is associated with an actin-binding protein, Kelch-like ECH-associated protein 1 (KEAP1), which retains NRF2 in the cytoplasm where it is targeted for ubiquitin-mediated degradation (28). KEAP1, a vital factor in the NRF2 signaling cascade, is a protein containing Kelch-1-like and BTB/POZ domains (29). Small amounts of constitutively nuclearly localized NRF2 maintain cellular redox homeostasis through regulation of basal expression of antioxidant genes.…”
mentioning
confidence: 99%
“…The Cul3 binding domain of Keap1 spans adjacent regions of the BTB and CLR domains. Keap1 contains a nuclear export signal, originating in the C-terminal end of the CLR, which is hypothesized to assist in the escort of Nrf2 from the nucleus (56).…”
Section: Introductionmentioning
confidence: 99%
“…A ChIP analysis in MDA-MB-231 cells did not detect Keap1 binding at the promoter of NQO-1, a xenobiotic response gene. 17 Similarly, no dKeap1 occupancy was detected at loci encompassing conventional xenobiotic response genes on polytene chromosomes (data not shown). Opposite effects of dKeap1 and CncC on transcription of xenobiotic response genes were revealed in our study and also previously reported.…”
Section: Dkeap1 On Chromatinmentioning
confidence: 87%
“…7,8 A small portion of nuclear Keap1 has been revealed in mammalian cells, 15 and was thought to transfer Nrf2 back to the cytoplasm after induction. 16,17 However, ubiquitinated Nrf2 is prominently nuclear in HepG2 cells. 16 We found that both dKeap1 and CncC predominantly localize to the nuclei of a number of Drosophila tissues, 11 suggesting that dKeap1 interacts with CncC mainly in the nuclei.…”
Section: Dkeap1 On Chromatinmentioning
confidence: 97%